ANALISIS ASPEK KENYAMANAN PEDESTRIAN JL CIKINI RAYA – JL PENATARAN KECAMATAN MENTENG DKI JAKARTA - Mardika, Dahkri Tri; Rahayu, Tuntun (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
Pedestrian space in the context of cities can play a role in creating a humane andenvironmentally friendly environment.. Pedestrian paths should be able to fulfill thecomfort of pedestrians by always considering all aspects of comfort and safety in everyplanning. Some aspects of comfort include circulation, accessibility, natural style andclimate, safety. cleanliness, beauty The analytical method used is descriptive analysis todescribe the existing condition of the route, aspects of comfort based on the comfortaspect. This research is in the Cikini Raya area up to the upgrading road